Visual bibliometric analysis of electroacupuncture research in stroke treatment: a 20-year overview - Chun, Hyonjun; Shin, Woo-Chul; Kim, Jong-min; Kim, Hyungsuk; Cho, Jae-Heung; Song, Mi-Yeon; Chung, Won-Seok (Frontiers in Neuroscience, 2023)
Background: Electroacupuncture has been used as a treatment; however, a visual bibliometric analysis has not yet been performed in this field. In this study, we aimed to suggest future research topics and directions related to the field by examining the last 20 years of research trends and hotspots of electroacupuncture in stroke.We searched the Web of Science database on electroacupuncture as a treatment for stroke published from 2003 to 2022. We analyzed the papers by annual publication, research fields, nations, affiliations, authors, journals, and keywords. VOSviewer software was used to visualize the bibliometric analysis and results. A total of 440 papers were included in the analysis.The number of publications has gradually increased every year, and neuroscience has become the most actively studied field. Neural Regeneration Research journal and China had the most publications. Fujian University of Traditional Chinese Medicine, as an affiliated institute, published the most articles. Chen Lidian and Tao Jing presented the largest number of papers, making them the leading contributors in this field. Four clusters were created by analyzing keywords, such as "neuroprotection," "clinical rehabilitation," "neuroplasticity," and "pretreatment-induced tolerance."This study is the first to analyze the research trends in electroacupuncture as a treatment for stroke using the VOSviewer. It shows the current state of research in the field by visualizing research trends and hotspots. This will help offer reference data for future studies. 1 2 Methods